Game-Based Learning in Improving Mathematical Problem-Solving Skills in Elementary School: A Systematic Literature Review - Salwa Pravitasari; Berta Apriza (Journal for Lesson and Learning Studies, 2026)
Mathematical problem-solving skills are among the higher-order thinking abilities that are essential to be developed in elementary school students. However, mathematics learning in elementary schools is still predominantly dominated by conventional approaches that emphasize procedural learning and memorization, resulting in limited student engagement and insufficient stimulation of analytical thinking skills. This study aims to analyze, evaluate, and synthesize empirical evidence regarding the effectiveness of Game-Based Learning (GBL) in improving elementary school students’ mathematical problem-solving skills. This study employed a Systematic Literature Review (SLR) method by referring to the PRISMA guidelines. The subjects of this study consisted of experimental and quasi-experimental research articles involving elementary school students, with a total of nine selected studies. Data were collected through documentation studies using data extraction sheets as the research instrument. The data were analyzed qualitatively through the processes of reduction, categorization, and synthesis of research findings. The findings indicate that the implementation of GBL, both digital and non-digital, consistently improves students’ mathematical problem-solving skills, particularly in understanding problems, planning solution strategies, and applying solutions. This study concludes that Game-Based Learning is a relevant pedagogical approach for supporting the development of higher-order thinking skills among elementary school students. The implications of this study suggest that the integration of GBL into mathematics learning can serve as an innovative alternative for creating more interactive, meaningful, and problem-solving-oriented learning experiences.